Analysis and Design of Cisco Packet Tracer Interconnections Between Autonomous Systems (AS) Using the Border Gateway Protocol at Campus 3 Khairun University - Saiful Do. Abdullah; Alan Wahyudin Nur; Hairil Kurniadi Siradjuddin; Rosihan; Adelina Ibrahim (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The purpose of the research is to analyze and design Autonomous System (AS) Interconnection using Border Gateway Protocol (BGP) at Campus 3, Khairun University. AS itself is an entity that plays an important role in a computer network consisting of several interconnected networks. BGP is a routing protocol used to exchange routing information between different ASes. The research methodology used includes a literature review to understand the concepts and basic principles of BGP and the relationship between ASes. Cisco Packet Tracer was later used as a simulation tool to design and implement interconnection scenarios between ASes at Campus 3, Khairun University. Analysis was conducted on network performance related to inter-AS connectivity, including latency, data transfer rate, and reliability. In addition, security aspects are also assessed to ensure the inter-AS connection at Campus 3, Khairun University is secure against cybersecurity attacks and threats. The results of this research will provide a better understanding of the relationship between AS and BGP implementation in a campus context. In addition, this research can also provide recommendations for improvements or enhancements to improve the performance and security of inter-AS connections at Campus 3 of Khairun University.